Country profile – Nigeria: Gender, climate change, and nutrition linkages - Iraoya, Augustine Okhale; Balana, Bedru; Thomas, Timothy S.; Ferguson, Nathaniel; Bryan, Elizabeth (International Food Policy Research Institute, 2025)
This country brief supports GCAN's goal of integrating gender, climate resilience, and nutrition considerations into policy by providing policymakers, program officers, and researchers with an analysis of Nige ria’s current situation and policy objectives in these areas. A recent study from Andam et al. (2023) underscores the vital role of Nigeria’s agrifood system in the country's economy. In 2019, Nigeria's Gross Domestic Product (GDP) stood at $469.3 billion, supported by a workforce of 66.8 million people (Andam et al. 2023). The agrifood sector made a substantial contribution, generating $175.3 billion in GDP and providing employment for 41.9 million individuals. This sector encompasses both primary agriculture and off-farm activities, including processing, trade, transport, food services, and input supply. Primary agriculture alone contributed $103.3 billion to GDP and employed 32.2 million people. Off-farm agrifood activities contributed approximately 40 percent of the agrifood GDP and 20 percent of agrifood employment (Andam et al. 2023).